Terapi Refleksi Al-Fatihah (Al-Fatihah Reflection Therapy) - Saktiyono B. Purwoko (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
Al Fatihah reflection Therapy (ART) is a theistic psychotherapy that shares characteristics with Cognitive Behavior Therapy (CBT) from Beck. However, the conceptualization and intervention emphasis differs in some ways. The ART has a vertical dimension (theistic) which uses the verses of Al Fatiha as a reflection of the changing thoughts, feelings, and behavior of individuals through restructuring cognitive, reading passages, and behavioral tasks. It is expected the ART can be applied, do research, and can be considered as a single intervention or additional interventionsfor Muslim clients.Keywords: Al-Fatihah, Reflection, Cognitive Restructuring, Verses Recitation, Behavioral Task.